Seasonal variability and coastal upwelling near Cape Santa Marta (Brazil) - Campos, Paula C. (2013)
The Santa Marta Grande Cape (CSM) area, a relatively steep and narrow continental shelf off southeast Brazil, is under the influence of the Brazil Current and intense seasonal variations of the wind field that affect the composition of water masses and their circulation. Hydrographic data, satellite-derived wind stress, and numerical simulations are used to characterize the seasonal and shorter period variability of the oceanographic conditions off CSM, in the area between 27S and 30S. The study is focused on the upwelling episodes and the dynamical mechanisms associated with these events. Field data and numerical results indicate significant seasonal changes in the oceanographic structure, the water mass composition, and the dynamical balance. During fall and winter, when southwesterly winds prevail and the frequency of meteorological frontal systems increases, the region is characterized by waters of continental origin, the Plata Plume Water (PPW). During spring and summer, deeper waters reach the surface layer due to the action of northeasterly winds. Coastal upwelling events are revealed by surface temperature minima observed south of CSM. Synoptic data show that these events occur in pulses associated with changes in the wind direction. Analysis of the numerical results shows that this particular location of the upwelling band results from the synergy between shelf-break upwelling and the regional shelf circulation induced by the northeasterly winds, both of which are modulated by changes in the coastline orientation and shelf width.